Association of daptomycin use with resistance development in Enterococcus faecium bacteraemia—a 7-year individual and population-based analysis. (February 2017) - Egli, A.; Schmid, H.; Kuenzli, E.; Widmer, A.F.; Battegay, M.; Plagge, H.; Frei, R.; Achermann, R.; Weisser, M.
Abstract: Objective: In this study we aimed to analyse the association between use of daptomycin and MICs of daptomycin in Enterococcus faecium bacteraemia. Methods: We prospectively enrolled patients aged ≥18 years with E. faecium bacteraemia hospitalized at the University Hospital Basel from 2008 to 2014. We determined daptomycin MICs by Etests and used pulsed field gel electrophoresis to determine clonal relatedness. We recorded the defined daily dosages of daptomycin (DDDs) per 100 patient-days and clinical data from charts. We correlated daptomycin MIC with use of daptomycin in patients with recurrence/persistence. Results: In 195 E. faecium bacteraemias originating from 162 patients the median MIC for daptomycin was 2 mg/L (IQR 2–3); 30% (15.4%) isolates had a MIC ≥4 mg/L and 6 (3.1%) were resistant (MIC >4 mg/L) according to CLSI criteria. The usage of daptomycin increased more than four-fold from 0.36 DDDs/100 patient-days in 2008 to 1.6 in 2014. In 13 of 28 (42.9%) patients with a relapsing or persisting bacteraemia, the daptomycin MIC of the second isolate increased from a median of 2.0 to 2.5 mg/L (p 0.010); 3/13 (23.1%) developed resistance. All patients with the same clone in the first and second episode and an increase of daptomycin MIC had been treated with daptomycin (6/6 versus 1/7 p 0.005). Conclusions: Daptomycin MICs and Daptomycin usage increased over time. On an individual patient level daptomycin exposure was associated with an increased MIC in subsequent bacteraemia episodes. Diversity did not indicate a clonal origin and argues for a de novo development of resistance.